2007
DOI: 10.1104/pp.106.093096
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Brassinosteroids and Related mRNAs in Pea Seed Growth and Germination

Abstract: The levels of endogenous brassinosteroids (BRs) and the expression of the biosynthesis/metabolism/perception genes involved have been investigated during the development and germination of pea (Pisum sativum) seeds. When seeds were rapidly growing, the level of biologically active BRs (brassinolide [BL] and castasterone [CS]) and the transcript levels of two BR C-6 oxidases (CYP85A1 and CYP85A6) reached a maximum, suggesting the significance of BL and CS in seed development. In the early stages of germination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
34
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 38 publications
5
34
1
Order By: Relevance
“…An important role for BR in plant reproductive growth and seed development has been suggested by the studies of BR-deficient and -insensitive mutants of Arabidopsis (Arabidopsis thaliana), pea (Pisum sativum), tomato (Solanum lycopersicum), and rice (Oryza sativa; Fujioka and Yokota, 2003;Nomura et al, 2007;Ye et al, 2010). In Arabidopsis, the weak BR-deficient mutant de-etiolated2 (det2;Fujioka et al, 1997) has lower fertility compared with the wild type (Ye et al, 2010), and the strong BR-deficient mutants dwarf4 (dwf4) and constitutive photomorphogenesis and dwarfism (cpd) are completely male sterile (Choe et al, 1998;Ye et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An important role for BR in plant reproductive growth and seed development has been suggested by the studies of BR-deficient and -insensitive mutants of Arabidopsis (Arabidopsis thaliana), pea (Pisum sativum), tomato (Solanum lycopersicum), and rice (Oryza sativa; Fujioka and Yokota, 2003;Nomura et al, 2007;Ye et al, 2010). In Arabidopsis, the weak BR-deficient mutant de-etiolated2 (det2;Fujioka et al, 1997) has lower fertility compared with the wild type (Ye et al, 2010), and the strong BR-deficient mutants dwarf4 (dwf4) and constitutive photomorphogenesis and dwarfism (cpd) are completely male sterile (Choe et al, 1998;Ye et al, 2010).…”
mentioning
confidence: 99%
“…Overexpression of a BR biosynthetic gene in rice increases seed filling and seed size (Wu et al, 2008). The BR-deficient mutant lk of pea has irregularly shaped seeds (Nomura et al, 2007). BR acts through the cell surface receptor BRASSINOSTEROID INSENSI-TIVE1 (BRI1; Kim et al, 2009) and transcription factors BRASSINAZOLE-RESISTANT1 (BZR1) and BRI1-EMS-SUPPRESSOR1 (BES1; Wang et al, 2002;Yin et al, 2002;He et al, 2005) to control a large number of BR-responsive genes (Sun et al, 2010b;Yu et al, 2011).…”
mentioning
confidence: 99%
“…Exogenous BR application rescued the low germination phenotype of GA-related mutants and BR-defective mutants are hypersensitive to ABA during early seedling development and stomatal closure [14][15][16] . Furthermore, the biologically active BR (brassinolide and castasterone) and BR biosynthetic gene expression were greatly increased during seed growth and germination of Pisum sativum (pea) 17 . BR signalling cascades are initiated from the plasma membrane-anchored co-receptors BRI1 and BAK1 (refs 18,19).…”
mentioning
confidence: 99%
“…4c, d) is accompanied by enhanced CYP85A2 expression (Castle et al 2005), and concomitant induction of the genes that encode the BRI1 and CYP85 orthologues has also been observed in germinating pea (Pisum sativum) (Nomura et al 2007). BRs have an important role in seed and fruit development (Huang et al 2013), and combined mRNA and BR analyses in various dicot species revealed that induction of the CYP85 genes during these processes results in transient accumulation of bioactive BRs (Montoya et al 2005;Nomura et al 2005Nomura et al , 2007Symons et al 2006). Taken together, these results support the notion that local induction of BR biosynthesis, and the resulting accumulation of the hormone, tends to coincide with enhanced BRI1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other phytohormones, BRs are not subject to active transport (Symons and Reid 2004;Montoya et al 2005), therefore, the concentration gradient required for eliciting differential responses is formed primarily by regulated local biosynthesis and deactivation of the hormone (Montoya et al 2005;Nomura et al 2007;Symons et al 2012). Variation of BR levels is controlled by homeostatic feedback regulation of the biosynthetic genes (Bancos et al 2002;Tanaka et al 2005) and feed-forward regulation of the deactivating genes (Choe et al 2001;Vert et al 2008), which limit the concentration range available for hormonal control.…”
Section: Introductionmentioning
confidence: 99%